Weipiling decoction alleviates N-methyl-N-nitro-N'-nitrosoguanidine-induced gastric precancerous lesions via NF-κB signalling pathway inhibition - Penghui Yang; Hongmei Yang; Hengli Zhou; Qiuyue Li; Sufen Wei; Qi Wang; Yan Yan; Yongqiang Liu; Huafeng Pan; Siyi Li (BMC, 2022)
Abstract Aim of the study We aimed to explore how weipiling (WPL) decoction WPL alleviates gastric precancerous lesions (GPLs) and uncover its anti-inflammatory roles in GPL treatment. Materials and methods The anti-GPL action mechanisms of WPL were analysed using a network pharmacological method. The WPL extract was prepared in a traditional way and evaluated for its major components using high-performance liquid chromatography with tandem mass spectrometry (HPLC-MS/MS). BALB/c mice were exposed to N-methyl-N-nitro-N-nitrosoguanidine (MNNG) (150 μg/mL) for 6 weeks to induce GPLs. GPL mice were administered WPL (3.75 g/kg/day and 15 g/kg/day) for an additional 8 weeks. Haematoxylin and eosin (H&E) staining was used to investigate histological alterations in gastric tissues. Expression of the T helper 1 (Th1) cell markers CD4+ and interferon-gamma (INF-γ) were tested using immunohistochemistry (IHC). Inflammatory protein and mRNA levels in the nuclear factor kappa B (NF-κB) pathway were detected using western blotting and a quantitative reverse transcription polymerase chain reaction (RT-qPCR), respectively. Results We identified and selected 110 active compounds and 146 targets from public databases and references. Four representative components of WPL were established and quantified by HPLC-MS/MS analysis. WPL attenuated MNNG-induced GPLs, including epithelial shedding, cavity fusion, basement membranes with asymmetrical thickness, intestinal metaplasia, dysplasia, pro-inflammatory Th1-cell infiltration, and INF-γ production, indicating that WPL prevents inflammation in the gastric mucosa. Furthermore, WPL reversed MNNG-induced activation of the IκB/NF-κB signalling pathway and subsequently attenuated the upregulation of inducible nitric oxide synthase (iNOS), cyclooxygenase-2 (COX-2), and nicotinamide adenine dinucleotide phosphate oxidase (NADPH oxidase (NOX)) family members NOX2 and NOX4. Conclusion WPL attenuated GPLs by controlling the generation of pro-inflammatory elements and inhibiting the NF-κB signalling pathway in vivo.